Use of response surface methodology for optimization of basal nutrients in production of amylase by streptomyces gancidicusasd_kt852565 - ASHWINI.K, (International Journal of Pharma and Bio Sciences, 2016)
Nutritional requirements at optimal level can contribute considerably to the production cost and the bioprocess economics. Media optimization using response surface methodology is one of the used methods to ameliorate the bioprocess economics. In the present study, Amylase production by Marine actinomycetes Streptomyces gancidicus_ASD was effectively enhanced by response surface methodology. An OFAT (one factor at a time) based statistical screening procedure was adopted to determine the most important factor affecting amylase production. The variables are screened and results show that sucrose and Beef extract concentrations influence the most as carbon and nitrogen source on amylase production respectively. A Central Composite Design was conducted to optimize the four selected factors. Statistical analyses of the data of model fitting were done by using Design expert 10.0(stat-Ease). Results show a maximum predicted Amylase yield of 11460.34 IU/ml when using 1.05 % sucrose, 0.608 % Beef extract, 7.1 pH and 40.35 °C Temperature. The predicted value is approximately 1.24 fold much higher than the original production (9248 IU/mL) determined by the conventional one-factor-at-a-time optimization method which can be applied in bioprocess for increased amylase yield.